Comparison Between C-MAC Blade D Video Laryngoscope and Macintosh Laryngoscope for Insertion of Double Lumen Tube in Patients Undergoing Elective Thoracic Surgeries - Sidra, .; Javed, Sidra; Baig, Mirza Shahzad; Ashraf, Iqra; Masroor, Layiba; Begum, Sumreen (Biological and Clinical Sciences Research Journal, 2025)
The insertion of a double lumen tube (DLT) for lung isolation during thoracic surgeries is technically challenging and may be associated with airway trauma and significant hemodynamic fluctuations. Video laryngoscopy, particularly with devices like the C-MAC blade D, has improved visualization and is increasingly employed to manage difficult airways. However, its efficacy compared to the conventional Macintosh laryngoscope in DLT intubation remains under investigation. Objective: To compare the performance of the C-MAC blade D video laryngoscope and the Macintosh laryngoscope for DLT intubation, focusing on intubation time and hemodynamic changes associated with laryngoscopy. Methods: A single-blind randomized controlled trial (ClinicalTrials.gov ID: NCT06759038) was conducted at the Department of Anesthesia, Shaheed Mohtarma Benazir Bhutto Institute of Trauma, from December 2024 to March 2025. Sixty adult patients (aged 18–60 years), classified as ASA I or II and scheduled for elective thoracotomy requiring DLT placement, were randomly assigned to either the C-MAC or Macintosh laryngoscope group. Only participants were blinded to group allocation. The primary outcome was the time taken for successful intubation. Secondary outcomes included intra-group and inter-group comparisons of hemodynamic parameters (heart rate, systolic and diastolic blood pressure) at baseline, during, and after intubation. Data were analyzed using SPSS version 26.0, with p < 0.05 considered statistically significant. Results: The mean intubation time was significantly longer in the C-MAC group (51.53 ± 7.25 seconds) compared to the Macintosh group (47.6 ± 5.46 seconds; p = 0.021). Although hemodynamic changes between groups were not statistically significant, within-group comparisons showed significant variations at different time points post-laryngoscopy. Conclusion: The Macintosh laryngoscope demonstrated superior performance in terms of shorter intubation time for DLT placement compared to the C-MAC blade D video laryngoscope. Both devices exhibited similar hemodynamic responses, suggesting comparable safety profiles. Further studies with larger sample sizes may validate these findings.